Chinese version of the Cancer Support Person's Unmet Needs Survey‐Sort Form: A psychometric study. (25th November 2018) - Han, Yuan; Zhou, Ying; Wang, Jing; Hall, Alix; Zhao, Qian; Qin, Huiying; Fan, Yuying; Song, Yalan; Cui, Shuzhong
Abstract: Objective: Psychometrically rigorous and comprehensive needs assessment measures for Chinese general cancer caregivers are relatively scarce. We described the development and psychometric evaluation of the Chinese version of the Cancer Support Person's Unmet Needs Survey‐Short Form (SPUNS‐SFC). Methods: A forward–backward translation method was utilised to develop the SPUNS‐SFC. The construct validity, internal consistency, convergent validity and discriminant validity of the SPUNS‐SFC were evaluated. Results: A total of 1, 026 Chinese cancer caregivers completed the SPUNS‐SFC. Items 10, 11, 13, 24 and 26 were removed as more than 80% of respondents reported having no unmet needs on these items. Exploratory factor analysis revealed a five‐factor structure, which accounted for 78.47% of the total variance, and consisted of the following domains: information, healthcare access and continuity, personal and emotional needs, worries about the future, and financial needs. Internal consistency of the measure was high, with Cronbach's alpha coefficients ranging from 0.87 to 0.95 for the five domains. The measure illustrated adequate evidence of convergent validity, demonstrated by significant correlations with multiple measures of psychological well‐being. Known‐groups validity was established, as 87.5% of the hypotheses were supported. Conclusion: This study indicates the SPUNS‐SFC is a reliable and valid measure of the unmet needs of Chinese cancer caregivers.